2015
DOI: 10.1016/j.jpowsour.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeability and economic aspects of alkaline zinc–manganese dioxide cells for electrical storage and load leveling

Abstract: h i g h l i g h t sZneMnO 2 battery was cycled at shallow DOD for more than 3000 cycles. Relatively low delivered cost of less than $150 per kWh. Mathematical model developed to understand the capacity fade mechanisms. Resistive film formation on the surface of MnO 2 particle during cycling. Change in SOC during cycling was used to measure capacity loss. Keywords:Rechargeable zincemanganese dioxide battery Cycle life ZneMnO 2 battery model Capacity fade model Film resistance a b s t r a c t Batteries based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
130
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 40 publications
3
130
0
1
Order By: Relevance
“…Major criteria for reversible cycling are to limit the depth of discharge to minimize the solubility of manganese in lower oxidation states, and to avoid the formation of soluble high oxidation state species during charging (i.e. MnO 4 2− ). 4,5,6,7 It has also been reported that the use of LiOH instead of KOH as the electrolyte can improve the cycle life of γ-MnO 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Major criteria for reversible cycling are to limit the depth of discharge to minimize the solubility of manganese in lower oxidation states, and to avoid the formation of soluble high oxidation state species during charging (i.e. MnO 4 2− ). 4,5,6,7 It has also been reported that the use of LiOH instead of KOH as the electrolyte can improve the cycle life of γ-MnO 2 .…”
mentioning
confidence: 99%
“…MnO 4 2− ). 4,5,6,7 It has also been reported that the use of LiOH instead of KOH as the electrolyte can improve the cycle life of γ-MnO 2 . 8 The structure of γ-MnO 2 is highly defective both in terms of type and concentration of defects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…> 4000 cycles at 5% DOD, 0.05 C rate; ∼3000 cycles at 10% DOD, 0.05 C rate; ∼2250 at 10% DOD, 0.1 C rate; ∼800 cycles at 10% DOD, 0.15 C; and ∼500 cycles at 20% DOD, 0.05 C rate). 19 It should be noted that the C-rates reported by Ingale et al were based on the cycled capacity of MnO 2 ; however, here they are reported based on the full 1 e − capacity of MnO 2 . For example, at 10% DOD cycling, a 0.2 C rate in this paper would be reported as 2 C in their work.…”
mentioning
confidence: 68%
“…In a full cell, TEA increases the discharge end voltage, rate performance, and energy efficiency as well as significantly increases the lifetime of the battery by 297%. Electrode preparation.-Electrodes were prepared with slight modification to the procedure described by Ingale et al 19 Battery cathodes were prepared by combining 65 wt% EMD, 30 wt% graphite, and 5 wt% PTFE solids with a mortar and pestle. EMD and graphite powders were mixed thoroughly, and then the PTFE dispersion was added and mixed until uniform.…”
mentioning
confidence: 99%